Dampak Budaya Kerja Pegawai pada Penerapan Aplikasi Simpel DPMPTP dalam Menigkatkan Pelayanan Publik di Kabupaten Padang Pariaman - Yhuni Arsa; Aldri Frinaldi (PUBLICNESS: Journal of Public Administration studies, 2022)
This study aims to determine the impact of employee work culture on the application of the DPMPTP simple application in improving public services in Padang Parimanan Regency. This research is a qualitative type with data analysis techniques Manual Data Analysis Procedure (MDAP). The results showed that the impact of employee work culture on the application of the DPMPTP simple application in improving public services in Padang Parimanan district had not yet had a good impact on employees according to the principle of Service Quality Dimensions based on E-Government. based on the results of the coding carried out that Category #1 Leadership; leadership is going well, Category #2 Appearance; the display has been designed as attractive as possible, Category #3 Awareness of time; Employees are aware of their respective duties and obligations, Category #4; Communication; Communication is well established, Category #5 Awards and Recognition; Lack of appreciation for employees, Category #6 Values and Trust; Trust has not been established, Category #7 Ease of Use; Usage is still disrupted due to the Simple which sometimes often crashes, Category #8; Trust; Lack of public trust, Category #9 Content and display of information; Still don't understand how to use the Simple application,  Category #10 Support; Lack of community participation in using simple programs.